Analysis of the influence of flexible and lubrication characteristics of main bearings on transmission error of RV reducers - ZHI Qiangong; NIU Linkai; XIONG Xiaoyan; YI Xianghong; YAN Shuai (Jixie chuandong)
ObjectiveThe RV reducer is extensively utilized in the joints of industrial robots due to its advantages such as the high reduction ratio, the low transmission error, and the compact structure. However, the main bearing, being a thin-walled bearing, is prone to significant deformation of the ring during the operation. The transmission error induced by the deformation of the flexible support cannot be neglected. Consequently, it is imperative to investigate the impact of the flexibility and lubrication characteristics of the main bearing on the transmission error of the reducer.MethodsTaking angular contact ball bearings as the research object, the parametric three-dimensional models of main bearings and reducers were established, and the multibody dynamic model of the rigid-flex coupling of main bearings, the elastic lubrication model of main bearings considering the flexible deformation of rings and the dynamic model of RV reducers were constructed. On the basis of studying the dynamic response of key parts of the reducer and the contact characteristics of the main bearing, the influence of the flexible characteristics of the main bearing on the transmission error of the RV reducer was further explored.ResultsThe results show that the transmission error range is -25.2″ to 21.6″ when the flexible characteristics of the main bearing are not considered, and the transmission error range increases to -43.2″ to 45″ after considering the flexible characteristics of the main bearing. With the increasing deformation of the ring, the transmission error of the reducer continues to increase; with the continuous increase of oil film thickness, the transmission error of the reducer first decreases and increases; with the continuous increase of oil film pressure, the transmission error of the reducer is also decreasing first and increases; the influence of the flexible characteristics of the main bearing on the transmission error of the reducer cannot be ignored, and it is of great significance to appropriately improve the supporting stiffness of the main bearing to reduce the transmission error of the RV reducer. The proposed method has certain reference significance for the precision design of RV reducers and main bearings.